The science of life written on birds second part : wattled curass ow (crax globulosa ) (2012)
Bilingual text Muinane-Spanish about the bird species niimɨku ‘Wattled Curassow’ (Crax globulosa), written by Aniceto Nejedeka, based on the knowledge of the elders of the Muinane tribe. This text is the second part of a book, titled “The science of life written on birds’, which we will be publishing is fascicles.